Effects of prenatal nutritional supplements on gestational weight gain in low- and middle-income countries: A meta-analysis of individual participant data - Liu, Enju; Wang, Dongqing; Darling, Anne M.; Perumal, Nandita; Wang, Molin; Ahmed, Tahmeed; Christian, Parul; Dewey, Kathryn G.; Kac, Gilberto; Kennedy, Stephen; Subramoney, Vishak; Briggs, Brittany; et al. (Elsevier, 2022)
Background: Gestational weight gain (GWG) below or above the Institute of Medicine (IOM) recommendations has been associated with adverse perinatal outcomes. Few studies have examined the effect of prenatal nutrient supplementations on GWG in low- and middle-income countries (LMICs). Objectives: We aimed to investigate the effects of multiple micronutrient supplements (MMSs) and small-quantity lipid-based nutrient supplements (LNSs) on GWG in LMICs. Methods: A 2-stage meta-analysis of individual participant data was conducted to examine the effects of MMSs (45,507 women from 14 trials) and small-quantity LNSs (6237 women from 4 trials) on GWG compared with iron and folic acid supplements only. Percentage adequacy of GWG and total weight gain at delivery were calculated according to the IOM 2009 guidelines. Binary outcomes included severely inadequate (percentage adequacy <70%), inadequate (<90%), and excessive (>125%) GWG. Results from individual trials were pooled using fixed-effects inverse-variance models. Heterogeneity was examined using I2, stratified analysis, and meta-regression. Results: MMSs resulted in a greater percentage adequacy of GWG [weighted mean difference (WMD): 0.86%; 95% CI: 0.28%, 1.44%; P < 0.01] and higher GWG at delivery (WMD: 209 g; 95% CI: 139, 280 g; P < 0.01) than among those in the control arm. Women who received MMSs had a 2.9% reduced risk of severely inadequate GWG (RR: 0.971; 95% CI: 0.956, 0.987; P < 0.01). No association was found between small-quantity LNSs and GWG percentage adequacy (WMD: 1.51%; 95% CI: −0.38%, 3.40%; P = 0.21). Neither MMSs nor small-quantity LNSs were associated with excessive GWG. Conclusions: Maternal MMSs were associated with greater GWG percentage adequacy and total GWG at delivery than was iron and folic acid only. This finding is consistent with previous results on birth outcomes and will inform policy development and local recommendations of switching routine prenatal iron and folic acid supplements to MMSs.